Disruptions in Primary School education in Guinea-Bissau - Carvalho, C.; Barreto, M. (European Conference of African Studies, 2019)
Disruptions in Primary School education in Guinea-Bissau, with Antónia Barreto, presentation at panel Soc06, European Conference of African Studies, Edinburgh, June 11-14 https://ecasconference.org/2019/panels#7626\